Effect of different energy and protein levels on growth performances and carcass yields of Sonali chicken - Jahan, M S; Hossain, A; Ahammed, M; Hossain, M E (Bangladesh Journal of Animal Science, 2024)
This study evaluated how varied energy and protein levels affect the growth and carcass traits of Sonali chickens. A 63-day experiment was conducted on 400-day-old Sonali chicks that were raised straight. The chicks were split into four groups of 100 birds apiece, which were then further separated into four subgroups of 25 birds each. The treatment groups were: T1 (2900 kcal/kg ME, 20% CP for starter and 3000 kcal/kg ME, 19% CP for grower); T2 (2900 kcal/kg ME, 21% CP for starter and 3000 kcal/kg ME, 20% CP for grower); T3 (2950 kcal/kg ME, 20% CP for starter and 3050 kcal/kg ME, 19% CP for grower) and T4 (2950 kcal/kg ME, 21% CP for starter and 3050 kcal/kg ME, 20% CP for grower) group. Sonali chicks were fed on starter diets from day old to 5 weeks of age and grower diets from 6 to 9 weeks of age. Results revealed that body weight was significantly (P<0.05) higher in the group having 2950 kcal/kg ME, 21% CP for starter and 3050 kcal/kg ME, 20% CP for grower at 9th weeks of age. In addition, FCR and total body weight gain showed significantly (P<0.05) better in the high nutrition group compared to other treated groups. Dressing percentage was numerically and abdominal fat was significantly (P<0.05) higher in the group having 2950 kcal/kg ME, 21% CP for starter and 3050 kcal/kg ME, 20% CP for grower compared to other groups. However, there were no significant differences (P>0.05) in skin, head, leg, liver, heart, gizzard, breast meat, drumstick meat, wing meat and thigh bone weight in relation to body weight among different dietary groups. Furthermore, despite the higher feed costs, the high nutrition group had higher selling price and profit margins per bird than the low nutrition diet. So, taken together, it can be concluded that a diet with high energy and high protein increases body weight and body weight gain and gives better FCR. Moreover, higher nutrition diet improves dressing yield, abdominal fat percentage and profit margins than the low nutrition diet. It is suggested that provision of energy (2950 kcal/kg ME for starter and 3050 kcal/kg ME for grower) and protein (21% CP for starter and 20% CP for grower) in the diet could be a potential energy and protein level for better performances of Sonali chicken. Bangladesh Journal of Animal Science 53(3): 101-110, 2024